(untitled) (Indonesian Economic Justice Review, 2024)
This paper examines the challenges faced by women entrepreneurs in Indonesia’s market economy, focusing on the gendered dimensions of economic justice. While Indonesia has made significant progress in encouraging women’s participation in the workforce, female entrepreneurs continue to encounter structural barriers that hinder their ability to access resources, markets, and opportunities. The study investigates the economic, legal, and social factors that limit women’s entrepreneurship, such as limited access to capital, gender-based discrimination, and cultural norms that restrict women’s economic agency. Drawing on case studies of women entrepreneurs in various sectors, including agriculture, retail, and technology, the paper analyzes how government policies and initiatives, such as microfinance programs and entrepreneurship training, have addressed or failed to address these challenges. The paper also examines the role of informal networks and social capital in supporting or hindering women’s business ventures. The findings suggest that while there has been progress in creating more opportunities for women entrepreneurs, gender inequality remains entrenched in many aspects of the business environment. The paper concludes with policy recommendations aimed at fostering gender-inclusive economic growth, including improving access to financing for women, promoting gender-sensitive business regulations, and challenging gender norms that limit women’s economic opportunities.